1995
DOI: 10.1093/genetics/139.2.697
|View full text |Cite
|
Sign up to set email alerts
|

Flamenco, a gene controlling the gypsy retrovirus of Drosophila melanogaster.

Abstract: Gypsy is an endogenous retrovirus of Drosophila melanogaster. It is stable and does not transpose with detectable frequencies in most Drosophila strains. However, we have characterized unstable strains, known as MG, in which it transposes at high frequency. These stocks contain more copies of gypsy than usual stocks. Transposition results in mutations in several genes such as ovo and cut. They are stable and are due to gypsy insertions. Integrations into the ovoD1 female sterile-dominant mutation result in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(43 citation statements)
references
References 32 publications
0
42
0
1
Order By: Relevance
“…The following strains were used: Canton S (wild type), flam A , w IR6RevII7 , Df(1)l11/FM7c B flam FM7 ; P{gypsy-lacZ.p12} [ 8 ] and flam BG02658 . Df(1)l11 deletion includes eor , flam , and wap genes [ 18 ]. Since the non-permissive flies carry the Bar ( B ) dominant mutation, these flies were distinguished from the permissive ones on the base of the dominant Bar phenotype of the eyes.…”
Section: Methodsmentioning
confidence: 99%
“…The following strains were used: Canton S (wild type), flam A , w IR6RevII7 , Df(1)l11/FM7c B flam FM7 ; P{gypsy-lacZ.p12} [ 8 ] and flam BG02658 . Df(1)l11 deletion includes eor , flam , and wap genes [ 18 ]. Since the non-permissive flies carry the Bar ( B ) dominant mutation, these flies were distinguished from the permissive ones on the base of the dominant Bar phenotype of the eyes.…”
Section: Methodsmentioning
confidence: 99%
“…2B). In both the feeding experiments and the genetic crosses, the assay of ovo D1 reversion, originally described by Mével-Ninio et al (21) and subsequently improved by identification of the flamenco gene as an essential element responsible for high level gypsy mobility (3,20), was used. The genetic crosses involved three steps.…”
Section: Isolation Of Ovo D1 Revertantsmentioning
confidence: 99%
“…A recent study in which three gypsy insertions into the ovo gene were sequenced (2) suggested that other target sequences could also be recognized, and suggested a relaxation of the proposed recognition sequence to YRYRYR. The gypsy element moves at high frequency during crosses of flamenco strains to other strains (20). A particularly useful genetic assay for gypsy movement was developed by Mével-Ninio et al (21), who found that dominant alleles of the X-linked ovo locus, such as ovo D1 , could be reverted by retrotransposon insertion.…”
Section: Introductionmentioning
confidence: 99%
“…However, a small number of koala and mouse clusters are enriched for antisense transposon insertions and produce transposon-mapping piRNAs with an antisense bias (e.g., Figure 2D; Wasik et al, 2015). These features are shared with the Drosophila flam cluster, which has an established function in transposon silencing in the somatic follicle cells of the ovary (Brennecke et al, 2007;Prud'homme et al, 1995). The three active endogenous retrotransposons in koala all produce antisense-biased piRNAs with ping-pong signatures (Figure 3E; Figure S5), but ERV.1 produces more antisense piRNAs than any other transposon subfamily.…”
Section: Does Transposition Into Clusters Enhance Antisense Pirna Pro...mentioning
confidence: 99%